Relationship between Characteristics of School Administrators and the Effectiveness of School under Primary Educational Service Area Office - Kobkarnna, Nathee; Bowngean, Chorphach; Nualsri, Masa (Journal of Local Governance and Innovation, 2019)
The purposes of this research were to 1) study characteristics of school administrators under Primary Educational Service Area Office 2) study the effectiveness of school under Primary Educational Service Area Office, and 3) study relationship between characteristics of school administrators and the effectiveness of school under Primary Educational Service Area Office. The sample used in this study were administrators and teachers schools under Primary Educational Service Area Office of 412 obtained. Random sample stratified random compare proportions and simple. Research methods: The research instrument used for collecting data was a 5-level rating scale questionnaire. The IOC is 1.00, the reliability of 0.99, the reliability of school administrators was 0.98 and the effectiveness of the school’s reliability was 0.98. The statistics used to analyze data were frequency, percentage, mean, standard deviation and Pearson product moment correlation coefficient. The research found that: 1) Characteristics of school administrators under Primary Educational Service Area Office in the overall was athigh levels. The highest average value was moral and ethical and the lowest was academic leadership. 2) The effectiveness of school under Primary Educational Service Area Office in the overall was at highest levels. The highest average value was achieving organizational objectives and the lowest was integration. 3) Relationship between characteristics of school administrators and the effectiveness of school under Primary Educational Service Area Office overall, there was a very high level of positive relationship with statistical significance at 0.01 level.